(untitled) (CIPEEX, 2026)
The contemporary environmental crisis has caused not only physical and ecological impacts, but also psychological ones, giving rise to a phenomenon called eco-anxiety. This is an emotional response to the perception of climate threat and imminent environmental destruction, which has intensified especially among young people. This study aims to analyze eco-anxiety as a psychological expression of malaise in contemporary civilization, based on its connection with the Freudian concept of the unfamiliar (Das Unheimliche). This is bibliographical research, using a deductive method, based on the classic works of Sigmund Freud—especially Civilization and Its Discontents (1930) and The Unfamiliar (1919)—as well as contemporary works on eco-anxiety and psychoanalysis. The results indicate that eco-anxiety should not be interpreted as an isolated pathology, but as a cultural symptom that expresses the return of the collective repressed about environmental destructiveness. The feeling of estrangement in the face of degraded nature recalls the Freudian experience of the unfamiliar, in which the once-familiar environment returns as a threat. It follows that eco-anxiety represents a legitimate indicator of contemporary psychological distress and requires clinical, social, and cultural approaches that recognize its symbolic dimension. Psychoanalysis, by integrating the unconscious, culture, and ecology, offers fundamental tools for understanding and processing this new malaise.